Microcapsules of grape peel extract as antioxidant vehicle: characterization, bioaccessibility and addition influence in meat model systems - Abraham Pajuelo; Carlos Folgado; Celia Moreno; Lenin Trujillo-Echeverría; Trinidad Perez-Palacios (Applied Food Research)
The objective of the present work was to develop and characterize grape peel extract microcapsules from advanced dispersion systems as antioxidant capacity vehicles to enrich meat products. To achieve this, the grape peel extract was firstly obtained and prepared according to each dispersion system: i) maltodextrin, ii) alginate, iii) double emulsion, iv) liposomes, followed by spray-drying, to obtain the corresponding microcapsule powders (MDM, AGM, DEM and LPM, respectively). Significant differences (p < 0.05) were observed in most of the analysed parameters among the different microcapsule types, although no single type of microcapsules achieved optimum values across all parameters. Liposome-based microcapsules were the most convenient, as they achieved satisfactory results for most quality parameters, especially microencapsulation efficiency (40.85 %), antioxidant capacity (0.011 mM Tolox, g microcapsules), and bioaccessibility (99.60 %). Due to that, this type of grape peel extract microcapsules was subsequently tested in meat model systems, minimally influenced on the usual changes that take during the processing or storage in dry-cured meat model systems, while it achieved to considerably increase the antioxidant capacity, oxidation stability and bioaccessibility of the natural antioxidant extract, thus, improving nutritional, functional and technological quality of the enriched meat product.